Spatial variability of heavy metal concentrations in vineyard soils on Malayer Plains (Iran). Issue 1 (2nd January 2016) - Solgi, Eisa; Solgi, Mousa; Rodríguez Martín, Jose Antonio
ABSTRACT: Accumulation of trace elements in arable soils is an important global hazard worldwide. Human activities, such as agriculture, are a continuous source of risk for heavy metal pollution that seriously disturbs the soil environment. In the present study, topsoil (0–20 cm) samples from vineyard soils in Malayer (Iran) were collected and analyzed for heavy metals, including Cu, Pb, and Zn by HR-CS FAAS. Compared with their levels in the earth's crust, these metals exhibited low concentrations. Variations in these metals were studied and geostatistics techniques were applied to generate spatial distribution maps. Empirical semivariograms can be simulated for the three heavy metals by spherical and linear models. The results of the statistical analyses (significant correlations among these metals) and their similar spatial distribution patterns indicate that Cu, Pb, and Zn probably derive from the same origin as their soil parent materials because of low levels of metals in vineyard soils. However, the high concentrations found in eastern-southern regions were probably created by anthropogenic influences, particularly application of manure and fertilizer.